Disaster resilient mesh network using LoRa and Nervenet - Lean, Chee Hong (2022)
When a natural disaster event happens, it could cause regional cellular network outages and hence disable network communication within the affected area. If a resilient network is implemented, alert messages with sufficient information can be sent over the Internet to provide a nationwide response. Japan National Institute of Information and Communication Technology has invented a resilient network framework called NerveNet, it supports mesh network where each node will approach other nodes in range if the current peer no longer responds. Using their technology, disaster nodes could be installed at disaster hotspots to send out disaster information or even provide light internet services. NerveNet does support data communication using Wi-Fi and LoRa. NerveNet Wi-Fi-Mesh links are used to provide wide bandwidth but low range data transmission, while NerveNet LoRa-Mesh supports narrow bandwidth data transmission in coverage of kilometers, which is suitable for crucial or emergency disaster data updates.